2014
DOI: 10.1007/s00253-014-6033-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculum sources on the enrichment of nitrite-dependent anaerobic methane-oxidizing bacteria

Abstract: Nitrite-dependent anaerobic methane oxidation (n-damo) is a newly discovered biological process that couples anaerobic oxidation of methane (AOM) to nitrite reduction. In this study, three different inocula, methanogenic sludge, paddy soil, and freshwater sediment were used to enrich n-damo bacteria in three sequencing batch reactors (SBRs), and three n-damo enrichment cultures, C1, C2 and C3, were obtained, respectively. After 500 days of incubation, Methylomirabilis oxyfera-like bacteria and n-damo activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 26 publications
3
19
3
Order By: Relevance
“…The denitrifying methanotrophic culture was originally enriched from paddy soil with natural freshwater medium for 18 months9 and artificial inorganic medium31 for the next 42 months. In the last 6 months, the concentrations of the trace elements iron and copper (important components of the key enzymes in the central metabolism) in the medium were increased to 20 and 10 μM, respectively, to accelerate the growth of the methanotrophs32.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The denitrifying methanotrophic culture was originally enriched from paddy soil with natural freshwater medium for 18 months9 and artificial inorganic medium31 for the next 42 months. In the last 6 months, the concentrations of the trace elements iron and copper (important components of the key enzymes in the central metabolism) in the medium were increased to 20 and 10 μM, respectively, to accelerate the growth of the methanotrophs32.…”
Section: Resultsmentioning
confidence: 99%
“…1), and these NC10 bacteria were physiologically active as denitrifying methanotrophs. Several enrichment cultures have indicated that group A members of the NC10 phylum perform AOM coupled to nitrite reduction45678910. Remarkably, the typical bacterium of the NC10 phylum, ‘ Candidatus Methylomirabilis oxyfera’ ( M. oxyfera ), utilizes oxygen produced from nitric oxide to intra-aerobically oxidize methane under anoxic conditions11.…”
mentioning
confidence: 99%
“…Two possible reasons may explain why members of groups B and E were eliminated during the enrichment process. First, the bacteria from groups B and E may mediate the process of AOM coupled to nitrite reduction, but the existing enrichment media or enrichment conditions were not appropriate for their growth, as discussed in previous literature (10). Second, members of groups B and E could not perform the process of AOM coupled to nitrite reduction or were not even methanotrophs.…”
Section: Figmentioning
confidence: 96%
“…Interestingly, only members of group A of the NC10 phylum were enriched, although three clusters of NC10 bacteria (scattered in groups A, B, and E) were detected in the inoculum. To date, researchers have obtained only group A-containing denitrifying methanotrophic cultures (3,8,10,(32)(33)(34)(35)(36)(37), and the functions of the members of NC10 phylum groups B, C, D, and E are unknown, although group B members were commonly detected in the inocula. Two possible reasons may explain why members of groups B and E were eliminated during the enrichment process.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation